Early modern improvisations
1 online resource.
Keywords: "With a panoramic sweep across continents and topics, Early Modern Improvisations is an interdisciplinary collection that analyzes the relationship between early modern literature and history through lenses such as gender, ethnicity, sexuality, religion, and politics. This volume is aimed at scholars and students alike who wish to explore early modern culture and its reverberations in ways that engage with a world outside the grand narratives and centralized institutions of power, a world that is more provisional, less scripted, and more improvisational"--